Dress and National Identity: Women's Clothing and the Celtic Revival. (June 2014) - Ward, Alex
<x content-type="archive" xml:space="preserve">Abstract</x> This paper will focus on an interesting diversion in the history of dress in Ireland: the story of clothing and the Irish cultural revival of the late nineteenth and early twentieth centuries. It will endeavour to address the ideology of so-called Irish costume, and how it was intended to be a visual symbol of an Irish renaissance, one which would help in the effort to counter British influences and establish a strong cultural identity. Although Celtic Revival clothing was worn by both men and women as a signifier of cultural and political sympathies, this paper will look specifically at women's dress and attempts to promote Irish costume as a tool for nation building, and as a practical solution to the wearing of imported fashions. It will highlight just some examples of where, when and by whom Celtic Revival dress was worn.